Investigations into the temperature related development of the Serpentine leaf miner Liriomyza trifolii (Burgess) on beans (Phaseolus vulgaris L.). - Heyer, Wolfgang; Richter, Siegfried (Contributions to Entomology = Beiträge zur Entomologie, 1990)
The duration and rate of development and the temperature sums and initial points of development of Liriomyza trifolii (Burgess) were determined under conditions of constant temperature. At 25°C on the ontogenesis takes 16 days. This puts teh daily rate of development at 6,25%. The temperature sums and initial points of development for the different stages are 40,8; 14,0 (egg), 31,5; 13,8 (larva), 107,4; 13,6 (pupa) and 172,5; 14,7 for the total development. The results obtained at the two places of investigation (Karl-Marx-Universität Leipzig, GDR and Institute for the Foundations of Tropical Agriculture, Santiago de las Vegas, Cuba) showed only slight differences.